Some results of the pacifc herring studies in the period of winter-spring fshery in the Okhotsk Sea - S. V. Loboda (Известия ТИНРО, 2018)
Pacifc herring stock was evaluated for two fshery districts in the Okhotsk Sea (North-Okhotsk and West-Kamchatka subzones) on the data collected during winter-spring fshery in 2017. The method of evaluation is described, quality of the materials collected aboard commercial fshing vessels is discussed, and the assessments are presented. Taking into account the areas of the districts and density of fsh distribution, the stock of herring is counted as 1854.92. 103 t (7390.36 . 106 ind.), mostly within the North-Okhotsk subzone (64.6 % by biomass). More than 90 % of this stock was formed by herring of commercial size that means that its juveniles were not counted properly by commercial catches. So, the stock assessment on the data of commercial catches could be used as additional method of the commercial stock monitoring, beyond the data of scientifc surveys.